2019
DOI: 10.1007/s10096-019-03708-7
|View full text |Cite
|
Sign up to set email alerts
|

Five-year Pan-European, longitudinal surveillance of Clostridium difficile ribotype prevalence and antimicrobial resistance: the extended ClosER study

Abstract: Clostridium difficile infection (CDI) has been primarily treated with metronidazole or vancomycin. High recurrence rates, the emergence of epidemic PCR ribotypes (RTs) and the introduction of fidaxomicin in Europe in 2011 necessitate surveillance of antimicrobial resistance and CDI epidemiology. The ClosER study monitored antimicrobial susceptibility and geographical distribution of C. difficile RTs pre-and post-fidaxomicin introduction. From 2011 to 2016, 28 European countries submitted isolates or faecal sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 22 publications
2
40
2
4
Order By: Relevance
“…The same distribution of the dominant C. difficile strains (027, 001/072 and 014/020) was found in the EUCLID study performed in Europe during 2012 and 2013, although the rate of 027 ribotype was lower than the one obtained in the present study [15]. In the last published study addressing C. difficile ribotypes Europe-wide, ribotype 027 remained the most prevalent, at the mean prevalence of 11.5% across 5 years, followed by ribotypes 001, 078, 014 and 020 [16]. On the contrary, in a recent study performed in North Macedonia, around 48% of isolates belonged to 001/072 [17].…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…The same distribution of the dominant C. difficile strains (027, 001/072 and 014/020) was found in the EUCLID study performed in Europe during 2012 and 2013, although the rate of 027 ribotype was lower than the one obtained in the present study [15]. In the last published study addressing C. difficile ribotypes Europe-wide, ribotype 027 remained the most prevalent, at the mean prevalence of 11.5% across 5 years, followed by ribotypes 001, 078, 014 and 020 [16]. On the contrary, in a recent study performed in North Macedonia, around 48% of isolates belonged to 001/072 [17].…”
Section: Resultscontrasting
confidence: 65%
“…As opposed to these results, Italy and Germany reported the increase in the rate of patients with ribotype 027 infection reaching 38% and 30%, respectively [23,24]. In Cyprus, its prevalence increased each year, from 28% in 2011 to 89% in 2015 [16].…”
Section: Resultsmentioning
confidence: 92%
“…The same distribution of the dominant C. difficile strains (027, 001/072 and 014/020) was found in the EUCLID study performed in Europe during 2012 and 2013, although the rate of 027 ribotype was lower than the one obtained in the present study (15). In the last published study addressing C. difficile ribotypes Europe-wide, ribotype 027 remained the most prevalent, at the mean prevalence of 11.5% across five years, followed by ribotypes 001, 078, 014 and 020 (16). On the contrary, in a recent study performed in North Macedonia, around 48% of isolates belonged to 001/072 (17).…”
Section: Resultscontrasting
confidence: 64%
“… 12 Fidaxomicin is already in therapeutic use in several countries and fidaxomicin-resistant C. difficile strains have been reported in rare cases. 17 Ridinilazole is currently in Phase III clinical trials; to date, no resistance to ridinilazole has been reported.…”
Section: Discussionmentioning
confidence: 99%